The Darkness Inside: the Freudian Concept of the Uncanny and its Romantic Roots - Molpeceres, Sara (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
In 1919 Sigmund Freud published The Uncanny, a key text to understand the aesthetic category of the uncanny. The roots of this category can be traced back to the German Romanticism, as Freud himself remarked. Nevertheless, even when Freud’s interpretation of the uncanny and the Romantic interpretation share the same ground, there are differences to be explored, differences related to the historical context of each author and their understanding of concepts such as symbol or reason. Thus, the paper focuses on the contrast between Romantic theories and Freudian theories, aiming to explain how the different interpretations evolve from the romantic authors to Freud.